Bhutan : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper discusses Bhutan's Poverty Reduction Strategy Paper (PRSP). The Royal Government of Bhutan has initiated the PRSP process as part of broader ongoing efforts to combat poverty. The main objective of the PRSP process is to strengthen the strategic framework for poverty reduction, improve donor coordination, and build support for new initiatives in public expenditure management and poverty monitoring and evaluation. The envisaged process builds directly on the Ninth Five-Year Plan (Ninth Plan).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet